European validation of a Cannabis sativa 13-locus STR multiplex kit for genetic identification: A preliminary study. Issue 1 (December 2019) - Di Nunzio, Michele; Roman, Madeline; Houston, Rachel; Di Nunzio, Ciro; Gangitano, David; Barrot-Feixat, Carme
Abstract: Cannabis sativa L. is a plant cultivated worldwide as a source of fiber, medicine and intoxicant. Traditionally, is divided into two main types: fiber type (hemp) and drug type (marijuana). Marijuana differs from hemp by the presence of a high quantity of the psychoactive drug, Δ9-tetrahydrocannabinol. The development of a validated method using short tandem repeats (STRs) could serve as an intelligence tool to link cases by means of genetic individualization or association of cannabis samples. For this purpose, a 13-locus STR multiplex method was developed, optimized, and validated by the Department of Forensic Science at Sam Houston State University (SHSU) according to relevant ISFG and SWGDAM guidelines. The European community considers C. sativa plants illegals, even though its consumption is accepted in precise and limited places (coffee shops or cannabis clubs in Netherlands and Spain). However, there are different gaps in the legislation of some European countries. For instance, in Italy, "weed" possession is decriminalized. Although trafficking and sale are prohibited, possession of small quantities of marijuana is considered only a civil offense. In order to proceed with the kit evaluation and inter-laboratory comparison, SHSU DNA laboratory sent blind cannabis DNA samples of known genotypes. Blind DNA samples were analyzed in different laboratories with different sequencers and analysis conditions. In this article, the goals were: a) to demonstrate that 13-locus STR kit for C. sativa is robust enough and reproducible, in all forensic laboratories, and b) to show the applicability of the STR system in association with Cannabis sativa cases for intelligence purposes to link multiple cases by means of genetic individualization or association of cannabis samples.